Highly dense composite luminescent material and method for preparing the same
Patent Information
- Application Number
- CN202211545292.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-24
- Filing Date
- 2022-12-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-12-05
AI Technical Summary
[0019]1.本发明提供一种高致密性外层包覆发光材料的复合材料,其能达到高耐热和高可靠度效能,可以应用于背光模块,有效提升液晶屏幕的Rec.2020大于90%(即色彩标准NTSC大于120%),其中Rec.2020为国际电信联盟无线电通信部门制定的超高清电视的色彩标准(ITU-R Recommendation BT.2020)。
Smart Images

Figure CN117447985B_ABST
Abstract
Description
Technical Field
[0001] A composite luminescent material, particularly a high-density composite coating that can effectively improve the reliability and lifetime of existing luminescent materials, such as quantum dot-light emitting diodes (QD-LEDs).
[0002] The primary application of the composite luminescent material provided by this invention, as described below, is as a coating for quantum dots and fluorescent materials. However, other related or similar luminescent materials may also be included within the scope of this invention, and are not limited thereto. Background Technology
[0003] Quantum dots, or nanoquantum dots, are artificial nanocrystals with semiconductor properties that range in size from 2 to 50 nanometers (nm). They can be used in a wide range of applications, including optical and electronic devices, military, industrial, medical, and commercial products, such as biomarking, catalysis, optical imaging, light-emitting diodes, and general lighting.
[0004] Quantum dots are applied to light-emitting diodes (LEDs). They absorb the light wavelengths of the LED chips and convert them into other light wavelengths, which are then mixed to form a white light source. This white light source can be used as the white light source for a display or as a single pixel in the display, which can enhance the brightness and color (color gamut) performance of the display. This is a major development focus for commercial applications.
[0005] Significantly improving the color performance of quantum dots is an important development goal for their application in high-end LCDs. At the same time, improving the heat resistance and reliability of existing quantum dots is one of the major challenges in current technological development. Summary of the Invention
[0006] In order to significantly improve the luminescence efficiency, heat resistance and reliability of existing quantum dots, the present invention provides a high-density composite luminescent material, which comprises a luminescent material uniformly coated in a high-density outer layer, the high-density outer layer comprising a sodium-poly(aluminum-oxygen-silicon) composite material.
[0007] The luminescent material includes quantum dots, quantum pillars, or fluorescent materials.
[0008] The quantum dot can be a single quantum dot, a double-layered or multi-layered core-shell quantum dot.
[0009] The quantum dot comprises cadmium selenide, cadmium sulfide, cadmium telluride, cadmium zincide, zinc selenide, zinc oxide, selenium sulfide, zinc sulfide, zinc telluride, mercuric sulfide, mercuric selenide, mercuric telluride, indium arsenide, indium phosphide, cesium lead halide (wherein the halogen may include chlorine, bromine or iodine) or a combination of the aforementioned quantum dot materials.
[0010] Furthermore, the quantum dot may also comprise cadmium selenide / cadmium sulfide, indium phosphide / cadmium selenide / cadmium sulfide, cadmium zinc sulfide selenium sulfide / zinc sulfide, indium phosphide / zinc sulfide, indium phosphide / zinc selenide, indium phosphide / zinc selenide / zinc sulfide, indium phosphide / zinc selenide / zinc sulfide selenium / zinc sulfide, silver indium sulfide, silver indium sulfide / zinc sulfide, or a combination of the aforementioned quantum dot materials.
[0011] The fluorescent material comprises visible light phosphor, near-infrared phosphor, or infrared phosphor and a combination thereof. The visible light phosphor comprises ytterbium aluminum garnet, lutetium garnet, gallium garnet, sulfide phosphor, or a combination thereof. The near-infrared phosphor or infrared phosphor comprises a host lattice phosphor, an activator, and a sensitizer.
[0012] The coating thickness of the highly dense outer layer ranges from 80 nm to 49.5 μm; the BET surface area of the highly dense outer layer ranges from 1 to 200 m². 2 / g; the pore volume of this highly dense outer layer is 0.001–0.1 cm³. 3 / g; or the particle size of the high-density composite luminescent material is between 100nm and 50μm.
[0013] This invention also provides a method for preparing the aforementioned high-density composite luminescent material, the steps of which include:
[0014] Step S1) Provide a luminescent material;
[0015] Step S2) The luminescent material is added to a reaction solution containing aluminum bis(sec-butanol) orthosilicate triethyl orthosilicate and a sodium-containing catalyst; and
[0016] Step S3) The reaction is continuously stirred so that the aluminum salt of bis(sec-butanol) orthosilicate triethyl orthosilicate and the sodium-containing catalyst are gradually synthesized into a highly dense outer layer of sodium-poly(aluminum-oxygen-silicon) composite material and several luminescent materials are encapsulated therein.
[0017] The sodium-containing catalyst contains sodium hydroxide, sodium borohydride, or sodium metaborate.
[0018] As can be seen from the above description, the present invention has the following beneficial effects and advantages:
[0019] 1. This invention provides a composite material with a highly dense outer layer coated with a light-emitting material, which can achieve high heat resistance and high reliability performance. It can be applied to backlight modules and effectively improve the Rec.2020 of the LCD screen by more than 90% (i.e., the color standard NTSC is more than 120%). Rec.2020 is the color standard for ultra-high-definition television (ITU-R Recommendation BT.2020) formulated by the Radiocommunication Sector of the International Telecommunication Union.
[0020] 2. The high-density composite luminescent material provided by this invention has been tested and found to effectively improve the reliability and lifespan of light-emitting diodes (LEDs), especially quantum dot light-emitting diodes (QD-LEDs), outperforming current international data. The manufacturing process of this invention is simple and reliable, and has significant market value and economic benefits. The resulting high-efficiency white QD-LED light source can be directly applied to the development of various terminal products such as white LED backlight modules. In response to the future demands of high-end LCD televisions, the use of quantum dots or suitable luminescent materials to improve color performance will allow consumers to enjoy nearly 50% more colors compared to current LCD televisions, contributing to innovation in fields such as entertainment, medical diagnostics, and e-commerce.
[0021] 3. The high-density nanocomposite outer layer of this invention can increase the photoluminescence quantum yield (Fold) by approximately 1.74 times, as well as the material's heat resistance and stability. By adding a sodium-containing catalyst during the solution-gel process, this invention can obtain a high-density, non-porous composite outer layer with the lowest specific surface area, and exhibits 133 mW at an input power of 2.4 mW. -1 The high luminous efficiency demonstrates the best reliability of QD-LEDs. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. It is reasonable and understandable that the accompanying drawings in the following description are merely some examples or embodiments of the present invention that are easy to understand and explain. For those skilled in the art, without making any progressive steps, the present invention can be applied to other similar or equivalent uses based on these drawings, all of which should be covered by the claims of the present invention. Unless it is obvious from the context or otherwise stated, the same reference numerals in the figures represent the same structures or steps, wherein:
[0023] Figure 1 This is a schematic diagram of a preferred embodiment of the high-density composite luminescent material of the present invention.
[0024] Figure 2 This is a schematic diagram of the process for preparing the highly dense composite luminescent material according to the present invention.
[0025] Figure 3 This is a schematic diagram of a first preferred embodiment of the application of the high-density composite luminescent material of the present invention in a luminescent device.
[0026] Figure 4 This is a schematic diagram of a second preferred embodiment of the high-density composite luminescent material of the present invention applied to a luminescent device.
[0027] Figure 5 This is a schematic diagram of a third preferred embodiment of the application of the high-density composite luminescent material of the present invention in a luminescent device.
[0028] Figure 6 This is a schematic diagram of a fourth preferred embodiment of the application of the high-density composite luminescent material of the present invention in a luminescent device.
[0029] Figure 7 The high-density composite luminescent material of this invention 29 silicon( 29 Si) nuclear magnetic resonance spectrum.
[0030] Figure 8 The high-density composite luminescent material of this invention 27 aluminum( 27 Al) nuclear magnetic resonance spectrum.
[0031] Figure 9 This is an electron image confirming that the highly dense composite luminescent material contains sodium.
[0032] Figure 10 This is the adsorption-desorption curve of the high-density composite luminescent material of the present invention.
[0033] Figure 11 Transmission electron microscopy images of examples with sodium borohydride (NaBH4) and examples without sodium borohydride (NaBH4) in this invention.
[0034] Figure 12 The photoluminescence spectra of the examples with added sodium borohydride (NaBH4) and the examples without added sodium borohydride (NaBH4) are shown in the present invention.
[0035] Figure 13 The time-resolved photoluminescence spectra of the sodium borohydride (NaBH4) example and several comparative examples are provided for this invention.
[0036] Figure 14 Luminous efficiency and lifetime reliability test results of preferred embodiments and several comparative examples of the present invention provided for addressing the effects of sodium borohydride (NaBH4) component.
[0037] Figure 15The results of luminous efficiency and lifetime tests of the preferred embodiments of the present invention and several comparative examples provided for different outer coatings are presented.
[0038] Figure 16 Temperature-dependent fluorescence spectra of sodium borohydride (NaBH4) examples and several comparative examples were provided for this invention. Symbol explanation:
[0039] 10 High-Density Composite Luminescent Materials
[0040] 11 quantum dots
[0041] 12 High-Density Outer Layer
[0042] S1~S3 Preparation Step 20 Reaction Solution
[0043] 30 Light-emitting device
[0044] 31 Packaging substrate
[0045] 32 chips
[0046] 34 Encapsulation substrate
[0047] 35 Isolation Layer
[0048] 36. LCD Module Structure Detailed Implementation
[0049] As illustrated in this invention, unless the context clearly indicates otherwise, the words "a," "an," "an," and / or "the" do not specifically refer to the singular and may also include the plural. Generally speaking, the terms "comprising" and "including" only indicate the inclusion of explicitly identified steps and elements, which do not constitute an exclusive list, and the method or apparatus may also include other steps or elements.
[0050] Flowcharts may be used in this invention to illustrate the operational steps performed by the method according to embodiments of the invention. It should be understood that preceding or following steps are not intended to limit the method steps provided by this invention to being performed precisely in sequence. Instead, the steps can be processed in reverse order or simultaneously. Furthermore, other steps can be added to these processes, or one or more steps can be removed from these processes to achieve the same or equivalent results.
[0051] <High-density composite luminescent materials>
[0052] Please refer to Figure 1This is a schematic diagram of a first preferred embodiment of the high-density composite luminescent material 10 provided by the present invention. It comprises a luminescent material 11 uniformly coated within a high-density outer layer 12. The luminescent material 11 can be at least one or more. The luminescent material 11 may include any quantum dot material or quantum pillar material. The quantum dot materials are either rods or fluorescent materials, with the size of the quantum dot materials ranging from 2 to 50 nm. The types include, but are not limited to, single quantum dot materials, such as cadmium selenide (CdSe), cadmium sulfide (CdS), cadmium telluride (CdTe), cadmium zinc sulfide (CdZn), zinc selenide (ZnSe), zinc oxide (ZnO), selenium sulfide (SeS), zinc sulfide (ZnS), zinc telluride (ZnTe), mercuric sulfide (HgS), mercuric selenide (HgSe), mercuric telluride (HgTe), indium arsenide (InAs), indium phosphide (InP), cesium lead halide (CsPbX3, Cs4PbX6, where X is Cl, Br, I), etc., or combinations of the aforementioned quantum dot materials; Alternatively, it can be a composite bilayer or multilayer core-shell quantum dot material, such as cadmium selenide / cadmium sulfide (CdSe / CdS), indium phosphide / cadmium selenide / cadmium sulfide (InP / CdSe / CdS), cadmium zinc sulfide selenium sulfide / zinc sulfide (CdZnSeS / ZnS), indium phosphide / zinc sulfide (InP / ZnS), indium phosphide / zinc selenide (InP / ZnSe), indium phosphide / zinc selenide / zinc sulfide (InP / ZnSe / ZnS), indium phosphide / zinc selenide / zinc sulfide selenium / zinc sulfide (InP / ZnSe / ZnSeS / ZnS), indium silver indium sulfide (AgInS2), indium silver indium sulfide / zinc sulfide (AgInS2 / ZnS), or combinations thereof.
[0053] The fluorescent material comprises visible light phosphors, near-infrared phosphors, or infrared phosphors, as well as combinations thereof. Visible light phosphors emit corresponding fluorescent light when irradiated with light in the visible light wavelength range (400–700 nm), while near-infrared or infrared phosphors emit corresponding fluorescent light when irradiated with light in the wavelength range (700–2500 nm).
[0054] The visible light phosphor contains ytterbium aluminum garnet (Y3Al5O3). 12 (YAG, yellow phosphor), lutetium garnet (LuYAG, yellow-green phosphor), gallium garnet (GaYAG, green phosphor), sulfide phosphor (SrS:Eu) 2+ SrGa2S4:Eu 2 + ZnS:Cu + (or a combination of the aforementioned fluorescent materials.)
[0055] The near-infrared phosphor or infrared phosphor preferably comprises a host lattice phosphor, an activator, and a sensitizer. The host lattice phosphor comprises any or any combination of compounds from Formula 1 to Formula 7.
[0056] EAGa 12 O 19 …Formula 1, where EA = magnesium (Mg), calcium (Ca), strontium (Sr) and / or barium (Ba).
[0057] A y Ga5O (15+y) …Equation 2, where A = lithium (Li), sodium (Na), potassium (K) and / or rubidium (Rb), y = 0.9-1.9.
[0058] AE3Ga2Ge4O 14 …Formula 3, where AE = magnesium (Mg), calcium (Ca), strontium (Sr) and / or barium (Ba).
[0059] Ln3Ga5GeO 14 …Formula 4, where Ln = lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and / or argon (Lu).
[0060] Ga2O3…Formula 5.
[0061] Ln3Ga 5.5 D 0.5 O 14 …Formula 6, where D = neodymium (Nd), germanium (Ge) and / or tantalum (Ta).
[0062] Mg4D2O9… Formula 7.
[0063] The activator and the sensitizer contain metal ions, such as trivalent chromium (Cr). 3+ ), trivalent ytterbium (Yb 3+ divalent nickel (Ni) 2 + ), trivalent terbium (Tb 3+ ), trivalent erbium (Er 3+ ) and / or trivalent thulium (Tm 3+ ( ) one or any combination thereof.
[0064] The near-infrared phosphor or infrared phosphor may also contain: K3AlF6:Cr 3+ MgO:Cr 3+ :Ni 2+La3Ga5GeO 14 :Cr 3+ ,Sc 0.98 BO3:Cr 3+ or K3GaF6:Cr 3+ .
[0065] The high-density outer layer 12 contains a sodium-poly(Al-O-Si) composite material.
[0066] A composite material is formed by encapsulating several of the luminescent materials 11 to form the high-density composite luminescent material 10 of the present invention. The high-density outer layer 13 is preferably a nanocomposite material, exhibiting a high-density structure with almost no pores on the surface, and the coating thickness is preferably between 80 nm and 49.5 μm. The particle size prepared can vary depending on the amount of each component material used in the preparation process, and is preferably between 100 nm and 50 μm.
[0067] <Preparation Method of High-Density Composite Luminescent Materials>
[0068] Please refer to Figure 2 The preparation method of the aforementioned high-density composite luminescent material 10 of the present invention includes the following steps:
[0069] Step S1) Provide the luminescent material 11;
[0070] Step S2) The luminescent material 11 is added to a reaction solution 20, which contains aluminum di-sec-butoxyaluminoxytriethoxysilane (DBATES) and a sodium-containing catalyst. The molar ratio of DBATES to the sodium-containing catalyst is between 1 and 1000 mmol: 1 and 2000 mmol. This ratio affects the particle size of the highly dense composite luminescent material 10 that can be prepared. If larger particles, such as 1 to 30 μm particles, are to be prepared, the concentration can be increased to between 10 and 1000 mmol: 20 and 2000 mmol. Conversely, if smaller particles, such as particles smaller than 1000 nm, are to be prepared, the concentration ratio can be between 1 and 10 mmol: 1 and 20 mmol.
[0071] Step S3) The reaction is continuously stirred at room temperature to gradually synthesize DBATES and the sodium-containing catalyst into the high-density outer layer 12 of sodium-poly(aluminum-oxygen-silicon) composite material and encapsulate several of the luminescent materials 11 therein.
[0072] In step S3, the ambient temperature range is preferably between 15 and 4°C, preferably between 20 and 35°C, or 25°C as used in this embodiment. The reaction time is preferably between 10 and 96 hours, preferably between 15 and 50 hours, or 24 hours as used in this embodiment. The reaction time is related to the thickness and density of the synthesized high-density outer layer 12.
[0073] The sodium-containing catalyst contains sodium hydroxide (NaOH), sodium tetrahydridoborate (NaBH4), or sodium metaborate (NaBO2).
[0074] Applications of high-density composite luminescent materials in light-emitting devices
[0075] Please refer to Figure 3 This is a schematic diagram of a first preferred embodiment of the present invention, in which the high-density composite light-emitting material 10 is applied to a light-emitting device 30. It includes an encapsulation substrate 31, a chip 32 disposed on the encapsulation substrate 31, and an encapsulation matrix 34 covering the chip 32. The high-density composite light-emitting material 10 of the present invention is distributed within the encapsulation matrix 34. In this embodiment, the light-emitting material used in the high-density composite light-emitting material 10 is quantum dots, forming a high-density composite quantum dot material (QDs@Na-poly(Al-O-Si)). In this embodiment, the encapsulation substrate 31 can be a plastic chip carrier, or more specifically, a plastic leaded chip carrier (PLCC). The encapsulation matrix 34 can be silicone resin.
[0076] Please refer to Figure 4 This is a schematic diagram of a second preferred embodiment of the present invention, in which the high-density composite light-emitting material is applied to the light-emitting device 30. Compared with the first preferred embodiment of the light-emitting device 30, this second preferred embodiment also includes the encapsulation substrate 31, the chip 32 disposed thereon, and the encapsulation substrate 34 covering the encapsulation substrate 34. However, in this embodiment, the high-density composite light-emitting material 10 is disposed on the encapsulation substrate 34 in the form of a film. Preferably, an isolation layer 35 is provided between the encapsulation substrate 34 and the film of the high-density composite light-emitting material 10, and also on the outside of the film.
[0077] Please refer to Figure 5This is a schematic diagram of a third preferred embodiment of the present invention applying the high-density composite light-emitting material to the light-emitting device 30. Compared with the first preferred embodiment of the light-emitting device 30, this third preferred embodiment also includes the encapsulation substrate 31 and the chip 32 disposed thereon, but in this embodiment, the encapsulation substrate 32 is not included, and the high-density composite light-emitting material 10 is also directly disposed or coated on all the chips 32 in the form of a single film. The high-density composite light-emitting material 10 is preferably covered by the isolation layer 35. The chip 32 and the high-density composite light-emitting material 10 film may contain other existing liquid crystal display module structure 36 (LCD module structure), which is not limited here.
[0078] Preferably, the light-emitting device 30 in Examples 1-3 is a general LED packaging structure, and the particle size of the high-density composite light-emitting material 10 used is preferably between 20 and 30 μm. In the process of manufacturing the high-density composite light-emitting material, in order to prepare larger particles, the concentration ratio of the reaction solution 20 is increased to 10-1000 mmol: 20-2000 mmol.
[0079] Please refer to Figure 6 This is a schematic diagram of a fourth preferred embodiment of the present invention applying the high-density composite light-emitting material to the light-emitting device 30. Compared with the aforementioned third preferred embodiment of the light-emitting device 30, this fourth preferred embodiment also includes the encapsulation substrate 31 and one or more chips 32 disposed thereon, and the high-density composite light-emitting material 10 is also in the form of a film, but is adaptively disposed on some or all of the chips 32. For example, if it is necessary for the light-emitting module 30 to emit white light, the high-density composite light-emitting material 10 of the present invention, which can emit white light, can be disposed on each chip 32; or if it is necessary for the light-emitting module 30 to emit different monochromatic light sources, the high-density composite light-emitting material 10, which can emit different colors of light, can be disposed on different chips 30 to achieve the effect of emitting different colors of light in the light-emitting device 30.
[0080] The high-density composite luminescent material 10 used in this embodiment preferably has a particle size of less than 1000 nm. To prepare smaller particles, the concentration ratio of the reaction solution 20 can be between 1–10 mmol: 1–20 mmol.
[0081] <Effectiveness Testing of High-Density Composite Luminescent Materials>
[0082] Please refer to Figure 7 It is the high-density composite luminescent material of this invention. 29 silicon( 29Si) nuclear magnetic resonance spectrum. From this nuclear magnetic resonance spectrum, the addition of this sodium-containing catalyst (NaBH4 in this example) can reveal a Q-value in the range of -80 ppm to -90 ppm. 4 (4Al) Aluminum silicate peaks, without the addition of NaBH4, can be detected at -85ppm to -95ppm with Q. 4 (3Al) Peak of aluminum silicate.
[0083] Please refer to Figure 8 The following table 1 shows the high-density composite luminescent material of the present invention. 27 aluminum( 27 Al) nuclear magnetic resonance spectrum. From 27 In the Al NMR spectrum, a spectrum covering q can be detected from -55 ppm to -75 ppm. 4 The peak of (4Si) aluminum silicate, from 27 The presence or absence of this sodium-containing catalyst in the Al NMR spectrum makes a difference. 27 Aside from the Al wave shift, the biggest difference lies in the integral area ratio of the nuclear magnetic resonance peak (NMR PEAK). The structure should contain two aluminum compounds, one is AlO4(4Si) and the other is AlO6. Therefore, it can be confirmed that the addition of this sodium-containing catalyst is necessary to achieve the effect of a highly dense composite material.
[0084] Table 1
[0085]
[0086] Please refer to Figure 9 Table 2 below shows an electron image confirming the presence of sodium in the high-density composite luminescent material of this invention. Table 2 lists the elements and their proportions contained in the high-density composite luminescent material of this invention, wherein the ratio of silicon to aluminum in this invention is between 1:2 and 1:4, while the ratio of silicon to aluminum in this embodiment is 1:2.85.
[0087] Table 2
[0088]
[0089]
[0090] Please refer to Figure 10 The adsorption-desorption curves of the high-density composite luminescent material of the present invention are shown in Table 3 below. The sodium-poly(aluminum-oxygen-silicon) composite material of this high-density composite luminescent material is an H4 type cycle, which is typically due to the presence of slit-like pores. Figure 9The document presents comparative examples and embodiment groups including those without and with the sodium-containing catalyst (using NaBH4 as an example). The comparative example without the sodium-containing catalyst has a BET surface area of 271.94 m². 2 / g, pore volume is 0.156cm³ 3 / g, pore size 0.6nm. The embodiment of the invention with added sodium-containing catalyst has a surface area of 2.39m². 2 / g, pore volume is 0.004cm³ 3 / g, with extremely small pores, indicates a denser outer layer. The BET surface area presented in various embodiments of the present invention ranges from 1 to 200 m². 2 / g, pore volume 0.001~0.1cm³ 3 / g.
[0091] Table 3
[0092]
[0093] Please refer to Figure 11 The images shown are transmission electron microscope (TEM) images comparing the results of adding sodium borohydride (NaBH4) and not adding sodium borohydride (NaBH4) in this invention. It can be seen that adding sodium borohydride results in a more dense structure, with a uniform distribution of the luminescent material 11. This highly dense composite luminescent material 10 exhibits a granular state, with a size ranging from approximately 100 nm to 50 μm. Different sample composition ratios are used depending on the application of different luminescent devices. Sodium borohydride (NaBH4) serves as the sodium-containing catalyst in this invention, accelerating the synthesis and density of the highly dense outer layer 12.
[0094] Please refer to Figure 12 Table 4 below shows the photoluminescence (PL) spectra of the present invention with sodium borohydride (NaBH4) and several comparative examples (containing pure quantum dots (Pristine QDs) and without sodium borohydride). The results show that the present invention exhibits better optical properties while enhancing the fluorescence stability of pure quantum dots. This test demonstrates that the highly dense outer layer can fill the surface defects of pure quantum dots, increasing the photoluminescence quantum yield (PLQY) by at least 1.74 times (fold).
[0095] Table 4
[0096]
[0097] Please refer to Figure 13Table 5 below shows the time-resolved photofluorescence (TRPL) plots of the examples of this invention with added sodium borohydride (NaBH4) and several comparative examples (containing pure quantum dots (Pristine QDs) and without added sodium borohydride). The results show that the examples of this invention have the best fluorescence lifetime (τ). avg ) and PLQY results.
[0098] Table 5
[0099] Comparative example (pure quantum dots) 8.37 Comparative example (without added sodium borohydride) 9.06 Example (with sodium borohydride added) 10.60
[0100] Please refer to Figure 14 This document presents lifetime test results (Reliability Analysis) of embodiments of the present invention with and without the addition of sodium borohydride (NaBH4) as the sodium-containing catalyst, along with several comparative examples (including pure quantum dots (Pristine QDs), no sodium borohydride, and existing silica-coated outer layers). The test conditions were 30°C / 60% RH and a blue light excitation energy of 24 mW @ 10 mA. Figure 14 The curves formed by solid cubes represent pure quantum dots (Pristine QDs), the curves formed by hollow circles represent quantum dots without added sodium borohydride (NaBH4), the curves formed by hollow stars represent a comparative example formed with an existing silica coating, and the curves formed by hollow rhombuses represent a preferred embodiment of the present invention. Figure 4 As can be seen, the present invention has the best luminous efficiency and the longest lifespan test results.
[0101] Please refer to Figure 15 This refers to the luminous efficiency and lifetime test results of preferred embodiments and several comparative examples of the present invention (including pure quantum dots (Pristine QDs), no sodium borohydride added, and existing silica-coated outer layers) provided for different coating outer layers. Figure 15 The curves formed by solid cubes represent pure quantum dots (Pristine QDs), the curves formed by hollow stars represent a comparative example formed with an existing silica coating, and the curves formed by hollow rhombuses represent a preferred embodiment of the present invention. Figure 15 It can be seen that the present invention has the best luminous efficiency and the longest lifespan test results compared with the existing technology.
[0102] Please refer to Figure 16This describes the temperature-dependent fluorescence spectra of the present invention with sodium borohydride (NaBH4) and several comparative examples (including pure quantum dots (Pristine QDs), no sodium borohydride, and existing silica-coated outer layers). When the luminescent material is used in LEDs (or particularly white LEDs (WLEDs)) as backlights for displays, the LED temperature increases with increasing operating drive current. In this test, the fluorescence intensity of the material was measured from 30 to 200°C. As the results show, the present invention exhibits superior thermal stability compared to other comparative examples.
[0103] In some embodiments, numbers describing the quantity of components and attributes are used. It should be understood that such numbers used in the description of embodiments are modified in some examples with the terms "approximately," "approximately," or "generally." Unless otherwise stated, "approximately," "approximately," or "generally" indicates that the numbers are allowed to vary by ±20%. Accordingly, in some embodiments, the numerical parameters used herein may be approximate values, which may be changed depending on the characteristics required by individual embodiments. In some embodiments, numerical parameters should take into account specified significant figures and employ a general method of preserving decimal places. Although the numerical ranges and parameters used to confirm their breadth of scope in some embodiments of the invention are approximate values, in specific embodiments, such numerical values are set as precisely as feasible.
[0104] Finally, it should be understood that the embodiments described in this invention are merely illustrative of the principles of the invention. Other modifications may also fall within the scope of this invention. Therefore, alternative configurations of the embodiments of this invention are considered as examples and not limitations, and are regarded as consistent with the teachings of this invention. Accordingly, the embodiments of this invention are not limited to those explicitly described and illustrated herein.
Claims
1. A highly dense composite luminescent material, characterized in that, The material comprises a luminescent material uniformly coated in a highly dense outer layer, the highly dense outer layer comprising a sodium-poly(aluminum-oxygen-silicon) composite material; The preparation method of high-density composite luminescent materials includes: Step S1) Provide a luminescent material; Step S2) The luminescent material is added to a reaction solution containing aluminum bis(sec-butanol) orthosilicate triethyl orthosilicate and a sodium-containing catalyst; Step S3) Continuous stirring of the reaction gradually synthesizes the aluminum salt of bis(sec-butanol) orthosilicate triethyl orthosilicate and the sodium-containing catalyst into a highly dense outer layer of a sodium-poly(aluminum-oxygen-silicon) composite material, encapsulating several luminescent materials therein, forming a highly dense composite luminescent material; and The sodium-containing catalyst contains sodium hydroxide, sodium borohydride, or sodium metaborate.
2. The high-density composite luminescent material as described in claim 1, characterized in that, The luminescent material contains quantum dots, quantum pillars, or fluorescent materials.
3. The high-density composite luminescent material as described in claim 2, characterized in that, The quantum dot can be a single quantum dot, or a double or multi-layered core-shell quantum dot.
4. The high-density composite luminescent material as described in claim 2 or 3, characterized in that, The quantum dot comprises cadmium selenide, cadmium sulfide, cadmium telluride, zinc selenide, zinc oxide, zinc sulfide, zinc telluride, mercuric sulfide, mercuric selenide, mercuric telluride, indium arsenide, indium phosphide, cesium lead halide, or a combination of the aforementioned quantum dot materials.
5. The high-density composite luminescent material as described in claim 2 or 3, characterized in that, The quantum dot comprises cadmium selenide / cadmium sulfide, indium phosphide / cadmium selenide / cadmium sulfide, indium phosphide / zinc sulfide, indium phosphide / zinc selenide, indium phosphide / zinc selenide / zinc sulfide, indium phosphide / zinc selenide / zinc sulfide, indium phosphide / zinc selenide / zinc sulfide selenium / zinc sulfide, silver indium sulfide, silver indium sulfide / zinc sulfide, or a combination of the aforementioned quantum dot materials.
6. The high-density composite luminescent material as described in claim 2 or 3, characterized in that, The fluorescent material comprises visible light phosphors, near-infrared phosphors, or infrared phosphors and combinations thereof.
7. The high-density composite luminescent material as described in claim 6, characterized in that, The visible light phosphor comprises ytterbium aluminum garnet, lutetium garnet, gallium garnet, sulfide phosphor, or a combination of the aforementioned fluorescent materials.
8. The high-density composite luminescent material as described in claim 6, characterized in that, The near-infrared phosphor or infrared phosphor comprises a host lattice phosphor, an activator, and a sensitizer, wherein: The host lattice phosphor comprises any or any combination of compounds from Formula 1 to Formula 5: EAGa 12 O 19 … Formula 1, where EA = magnesium (Mg), calcium (Ca), strontium (Sr) and / or barium (Ba); A y Ga5O (15+y) … Equation 2, where A = lithium (Li), sodium (Na), potassium (K) and / or rubidium (Rb), y = 0.9-1.9; AE3Ga2Ge4O 14 … Equation 3, where AE = magnesium (Mg), calcium (Ca), strontium (Sr) and / or barium (Ba); Ln3Ga5GeO 14 … Equation 4, where Ln = lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and / or lutetium (Lu); Ga2O3… Formula 5; and The activator and the sensitizer contain trivalent chromium (Cr). 3+ ), trivalent ytterbium (Yb 3+ divalent nickel (Ni) 2+ ), trivalent terbium (Tb 3+ ), trivalent erbium (Er 3+ ) and / or trivalent thulium (Tm 3+ ( ) one or any combination thereof.
9. A method for preparing a highly dense composite luminescent material, characterized in that, The steps include: Step S1) Provide a luminescent material; Step S2) The luminescent material is added to a reaction solution containing aluminum bis(sec-butanol) orthosilicate triethyl orthosilicate and a sodium-containing catalyst; Step S3) Continuous stirring of the reaction gradually synthesizes the aluminum salt of bis(sec-butanol) orthosilicate triethyl orthosilicate and the sodium-containing catalyst into a highly dense outer layer of a sodium-poly(aluminum-oxygen-silicon) composite material, encapsulating several of the luminescent materials therein, forming a highly dense composite luminescent material as claimed in any one of claims 1 to 8; and The sodium-containing catalyst contains sodium hydroxide, sodium borohydride, or sodium metaborate.
Citation Information
Patent Citations
Silica-coated quantum dots and preparation method thereof
CN107474821A
Metal oxide / silicon dioxide cladded or packaged quantum dot, and preparation method thereof
CN107541203A